FAKTOR PENENTU KEBIJAKAN UTANG PADA PERUSAHAAN KONSUMER NON-SIKLIKAL YANG TERDAFTAR DI BEI - Lesmana, Gabriel Efrant; Widyasari, Widyasari (Jurnal Paradigma Akuntansi, 2025)
This study aims to empirically test what factors that have an influence on debt policy of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange. The data used in this study is secondary data obtained from the Indonesia Stock Exchange during the 2018-2021 period. The sample selection technique applied in this study was a purposive sampling technique. From purposive sampling method, 25 companies were obtained according to criteria that has been determined in this study. Data processing in this study was assisted with software from Eviews 10.0 and Microsoft Excel using multiple regression analysis with total sample for 4 years of 100 samples. The results of this study shows that profitability and managerial ownership have a negative and significant influence on debt policy. Meanwhile, institutional ownership and company growth do not significantly influence debt policy.